Screening for novel endogenous inflammatory stimuli using the secreted embryonic alkaline phosphatase NF-κB reporter assay - Zuliani-Alvarez, Lorena; Piccinini, Anna M.; Midwood, Kim S. (Bio-protocol LLC, 2017)
An immune response can be activated by pathogenic stimuli, as well as endogenous danger signals, triggering the activation of pattern recognition receptors and initiating signalling cascades that lead to inflammation. This method uses THP1-Blue™ cells, a human monocytic cell line which contains an embryonic alkaline phosphatase reporter gene allowing the detection of NF-κBinduced transcriptional activation. We validated this protocol by assessing NF-κB activation after stimulation of toll-like receptor 4 (TLR4) by two different agonists: lipopolysaccharide (LPS), derived from the cell wall of Gram negative bacteria, and tenascin-C, an extracellular matrix protein whose expression is induced upon tissue injury. We then used this protocol to screen for potential new endogenous TLR4 agonists, but this method can also be used as a quick, economical and reliable means to assay the activity of other inflammatory stimuli resulting in TLR-dependent NF-κB activation.